Beyond the Rio Gila [large type] - Hibbard, Scott G. (Wheeler Publishing, a part of Gale, a Cengage Company, 2021)
"In 1846, the Mexican-American War cast together Latter-day Saits fleeing persecution and the U.S. Army. The Mormon Battalion must march two thousand miles. Among the army's First Dragoons, Moses Cole, a Virginia farm boy running from his abusive father, grows to manhood under the mentorship0 of a tormented alcoholic and former professor. Among the Mormons, Orson Everett teaches his colorful followers to work for their brethren with God in their hearts. On such a journey, some will thrive, some will perish, all will be transformed. This deeply researched depiction of the U.S. military's longest march brings a little known yet uniquely American story to life." - back cover